Advances in Visual Computing 5th International Symposium, ISVC 2009, Las Vegas, NV, USA, November 30 - December 2, 2009, Proceedings, Part I - Boyle, Richard; Parvin, Bahram; Koracin, Darko; Kuno, Yoshinori; Wang, Junxian; Renato, Pajarola; Lindstrom, Peter; Hinkenjann, Andre; Encarnacao, Miguel L.; Silva, Claudio T.; Coming, Daniel (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2009)
The two volume set LNCS 5875 and LNCS 5876 constitutes the refereed proceedings of the 5th International Symposium on Visual Computing, ISVC 2009, held in Las Vegas, NV, USA, in November/December 2009. The 97 revised full papers and 63 poster papers presented together with 40 full and 15 poster papers of 7 special tracks were carefully reviewed and selected from more than 320 submissions. The papers are organized in topical sections on computer graphics; visualization; feature extraction and matching; medical imaging; motion; virtual reality; face processing; reconstruction; detection and tracking; applications; and video analysis and event recognition. The 7 additional special tracks address issues such as object recognition; visual computing for robotics; computational bioimaging; 3D mapping, modeling and surface reconstruction; deformable models: theory and applications; visualization enhanced data analysis for health applications; and optimization for vision, graphics and medical imaging: theory and applications.